PRODUCTION OF AGENTS FOR BIOCONTROL OF APPLE FUSARIUM ROT BY SOILBORNE STREPTOMYCETES: Received: 16th June 2021; Revised: 2nd November 2021, 10th January 2022, 13th January 2022; Accepted: 17th January 2022 - Mitrović, Ivana; Grahovac, Jovana; Dodić, Jelena; Grahovac, Mila; Trivunović, Zorana; Dodić, Siniša (MATTER: International Journal of Science and Technology, 2022)
Within this paper, the potential of Streptomyces hygroscopicus in biocontrol of two isolates of Fusarium avenaceum isolated from apple fruits in the storage was tested. Production of S. hygroscopicus biocontrol agent was performed in 3 l stirred tank bioreactor at an aeration rate of 1.5 vvm and mixing speed of 150 rpm. Bioprocess was realized at 26 ±1°C for 168 hours. The activity of bioagents production was tested using in vitro diffusion method with wells. Also, residual glycerol, residual nitrogen content, and cell biomass were determined to analyze bioprocess parameters. The results showed that the highest production of bioagents was observed in 96h of cultivation when the largest zone diameters were formed against F. avenaceum KA12 and KA13 of 40.67±1.15 and 43.33±0.58 mm, respectively. The activity of the produced bioagents was confirmed in in planta research, where the difference between necrosis diameter of treated and control samples were 2.79 (for KA12) and 2.17 (for KA13) times smaller.